Paths toward the nation : Islam, community, and early nationalist mobilization in Eritrea, 1941-1961 - Venosa, Joseph L. (Athens : Ohio University Press, 2014)
In the early and mid-1940s, during the period of British wartime occupation, community and religious leaders in the former Italian colony of Eritrea engaged in a course of intellectual and political debate that marked the beginnings of a genuine national consciousness across the region. During the late 1940s and 1950s, the scope of these concerns slowly expanded as the nascent nationalist movement brought together Muslim activists with the increasingly disaffected community of Eritrean Christians. The Eritrean Muslim League emerged as the first genuine proindependence organization in the cou.
Islam, community, and the cultural politics of Eritrean nationalism -- Early rumblings : Muslim activism in British-occupied Eritrea, April 1941-November 1946 -- Founding success : the Muslim League and the early nationalist movement, November 1946-December 1947 -- Navigating rough seas : the Muslim League's internal challenges, January 1948-September 1949 -- Maintaining momentum : the Muslim League and its rivals, September 1949-December 1950 -- Holding the line : institutional autonomy and political representation on the federation's eve, December 1951-September 1952 -- Struggling for autonomy : the disintegrating federation, October 1952-December 1957 -- New beginnings at the federation's end : Muslim mobilization, popular resistance, and diaspora activism, January 1958-September 1961.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 072
Keywords: Eritrea -- History -- 20th century; Eritrea -- Politics and government -- 1941-1952.; Eritrea -- Politics and government -- 1952-1962.; Islam and politics -- Eritrea; Muslims -- Political activity -- Eritrea; HISTORY -- Africa -- East; Islam and politics; Muslims -- Political activity; Politics and government; Eritrea; RELIGION / Islam / General; 1900-1999; Electronic books; History